2019
DOI: 10.1002/jcu.22722
|View full text |Cite
|
Sign up to set email alerts
|

Utility of indirect sonographic signs (including cavum septum pellucidum ratio) in midgestational screening for partial agenesis of corpus callosum

Abstract: Purpose This study was undertaken to evaluate the performance of indirect sonographic signs in detecting partial agenesis of the corpus callosum (pACC) at midgestation, focusing on the cavum septum pellucidum (CSP) ratio. Methods A retrospective case‐controlled study of singleton pregnancies was conducted, examining fetuses diagnosed with isolated pACC and normal controls. At midgestational age, fetal head volumes were imaged with 3D US and stored for the evaluation of indirect sonographic findings in axial pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…An initial qualitative analysis of 27 studies was performed. After this initial analysis, three studies published prior to 1990 were excluded, yielding a total of 24 studies included in the final analysis 12–35 . Table S2 shows a summary of the studies using the PICOS framework as a guide.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An initial qualitative analysis of 27 studies was performed. After this initial analysis, three studies published prior to 1990 were excluded, yielding a total of 24 studies included in the final analysis 12–35 . Table S2 shows a summary of the studies using the PICOS framework as a guide.…”
Section: Resultsmentioning
confidence: 99%
“…In the early 1990s, dedicated fetal neurosonography was added to the diagnostic work-up, and fetal MRI 12 Bennett (1996) 13 d'Ercole (1998) 14 Glenn (2005) 15 Volpe (2006) 16 Manfredi (2010) 17 Lerman-Sagie (2009) 18 Cignini (2010) 19 Ghi (2010) 20 Paladini (2013) 21 Pashaj (2015) 22 Craven (2015) 23 Alby (2016) 24 R üland (2015) 25 Shen (2015) 26 Shinar (2016) 27 Manganaro (2017) 28 Karl (2017) 29 Manevich-Mazor (2018) 30 Zhao (2019) 31 Turkyilmaz (2019) 32 Santirocco (2021) 33 Meidan (2019) 34 Jarre (2017) 35 Only first author of each study is given. A maximum of four stars could be given for selection, two for comparability and three for outcome.…”
Section: Imaging Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as discussed, an anomaly of the CSP was another neuroanatomical feature that reported within, and at times out of the isolated diagnosis of ACC. The authors of three studies specifically examined the CSP within fetuses with partial ACC, and concluded that the atypical presentation of the CSP might be considered an indirect sign of partial ACC (Karl et al, 2017;Shen et al, 2015;Zhao, Wang, & Cai, 2019). Griffiths et al, (2009) reflected on their experience and embryology and concluded that displacement or abnormality of the septum pellucidum was typical of ACC, as opposed to an absence, again suggestive of differences in interpretation.…”
Section: Neuroanatomy Additional Anomalies and Causes Of Accmentioning
confidence: 99%
“…Prenatal care and examination are crucial for gravidas to ensure healthy newborns. Congenital abnormalities of the central nervous system (CNS) are a major concern in prenatal detection of fetal brain ( 1 ), which can be screened by ultrasound (US) as a safe, cost-effective, and real-time imaging modality. Evaluation of the corpus callosum (CC) and cerebellar vermis (CV) are critical aspects of fetal brain examination.…”
Section: Introductionmentioning
confidence: 99%